Force and velocity of impact during upper limb strikes in combat sports: a systematic review and meta-analysis - Beránek, Václav; Votápek, Petr; Stastny, Petr (Sports biomechanics, 2023)
Upper limb strikes are frequent movements in combat sports and self-defence systems, in which numerous types of strikes can be applied. Therefore, the aim of this systematic review and meta-analysis was to summarise and compare the mechanical consequences of different types of upper limb strikes among various sports disciplines. A literature search was conducted in Scopus and Web of Science, with the following search formula: (impact force) AND (strike) AND (taekwondo) OR (karate) OR (self-defence) OR (combat sport) OR (boxing). The search resulted in 28 studies describing 9 kinds of strikes, where straight punches and reverse punches have larger mean impact forces than the kung fu punch (p < 0.001) and that a palm strike had a lower strike velocity (p < 0.001) than a reverse punch, straight punch, or junzuki punch. The highest recorded mean force was found for a straight punch (3427 N). Athletes in mixed martial arts, trainers of self-defence or tactical coaches can expect that straight punches and reverse punches should be performed at high speeds (over 10 m/s) and provide similar or larger impacts than other upper limb strikes; therefore, those punches should favour a combat athlete to win a competition or succeed in self-defence.
Keywords: Upper Extremity; straight punch; biomechanika; Biomechanical Phenomena; bojové sporty; low punch; sportovci; horní končetina; Humans; Martial Arts; pohyb; Box; mixed martial arts; Athletes; lidé; Movement; side punch